Extracorporeal Membrane Oxygenator (ECMO) for Life Support in Fulminant Myocarditis - Aranwutikul, Darin; Lertbunrian, Rojanee; Lumpaopong, Adisorn; Katanyuwong, Poomiporn; Gunyaphan, Sombat; Numchaisir, Jule; Khongphatthanayothin, Apichai (The Bangkok Medical Journal, 2013)
Fulminant myocarditis refers to acute myocarditis with abrupt onset of severe cardiogenic shock and circulatory collapse. Once regarded as a disease with uniformly high mortality, fulminant myocarditis is now a potentially treatable condition, thanks to advances in intensive care and mechanical circulatory support. We report our first pediatric case of fulminant myocarditis rescued by extracorporeal membrane oxygenator (ECMO) and continuous renal replacement therapy (CRRT).